Relationship Marketing: A Conceptual Analysis - Bansal, Harbhajan; Smriti, Komal (Indian Journal of Marketing, 2008)
Since the beginning of the phenomenon of marketing, there have been many changes in the business scenario, practically and academically. Over a long period of time, different concepts and conceptions have come into being and have been replaced by some other ones, yet the two aspects that have remained unchanged are - marketer and customer. Marketer plans and directs all the efforts towards the customers, and they know it intrinsically that their survival and well-being are in the hands of the customer. This inter-relationship shapes the structure of an organization, society and economy. Though both the parties hold equal importance, yet the role of marketer is more or less reactive, and the centre stage is held by the customer.